From Hospital To Home: The Seamless Transition Facilitated By Nurses And Social Workers (Journal of Namibian Studies : History Politics Culture, 2022)
This article explores the collaborative efforts of nurses and social workers in facilitating the transition of patients from hospital to home. The transition period poses significant challenges for patients, necessitating comprehensive support to ensure a smooth adjustment and continuity of care. Through interdisciplinary assessment, personalized care planning, patient education, and coordination of services, nurses and social workers address medical, social, and emotional needs.